Vitamin A fortification: key factors and considerations for effective implementation - Han, Joohun; Durand-Morat, Alvaro; Mottaleb, Khondoker (Frontiers in Public Health, 2025)
Vitamin A fortification plays a crucial role in achieving long-term economic development in developing countries by supporting the growth and development of human capital. While fortification programs involve a range of nutritional, agricultural, economic, and political considerations, there is a lack of a comprehensive overview of the topic in the literature. Our review highlights the importance of holistic approach in designing fortification programs: the effective program should consider (a) the agronomic, economic, and administrative capability of the target regions in regard of fortification method and vehicle to maximize effectiveness; (b) strategies to ensure the producers' and consumers' adoption to enhance uptake rate; and (c) evaluate outcomes with respect to economic metrics rather than focusing solely on before-and-after comparison to avoid biased assessment.